Amaliyah Tadris: Teacher Education Training Program for Santri - Majid, Nur Kholis; Subakri, Subakri; Sukamto, Sukamto; Nofiyanata, Dwi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The amaliyah tadris program is implemented to identify and develop the competence of teachers or ustadz early on, through learning practices carried out by students. This is important to improve the quality of teaching in modern boarding schools, which has a direct effect on the progress of santri (student) education. This study aims to analyze how the implementation of amaliyah tadris activities as a teacher education provision program for santri. The research method in this study uses a qualitative method with a case study approach. Data collection in this study used observation, interview and documentation techniques, data analysis in this study used Miles & Huberman interactive analysis techniques which included data collection, data condensation, data presentation and verification or conclusion drawing, checking the validity of the data in this study using triangulation techniques. The results of the research indicate that the implementation of amaliyah tadris activities is effective in building the pedagogical competence of santri as prospective educators. This activity succeeds in preparing santri well through a combination of knowledge, theory, and direct practice, so that they can be better prepared to become ustadz or teachers in the future. Significantly, amaliyah tadris activities also contribute to honing the mentality of santri as educators, improving their ability to use foreign languages (Arabic and English) in learning, and strengthening their skills in managing discussions and responding more actively to learning dynamics. This implication shows that amaliyah tadris not only equips santri with knowledge, but also prepares them practically to carry out their role as professional educators. The new finding of this study is that amaliyah tadris activities not only serve as theoretical provision, but also equip santri with practical skills in managing learning that involves the use of foreign languages and increased interaction with learners.